2016
DOI: 10.1080/09712119.2016.1257431
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary colostrum powder on performance, carcass yields and serum lipid peroxidation levels in Japanese quails (Coturnix coturnix japonica)

Abstract: Colostrum is a nutrient-dense fluid secreted by female mammals for the first few days following birth. Colostrum can be supplemented to poultry diets as a feed additive due to its nutritious and performance-enhancing properties. This study was conducted to determine the effect of dietary colostrum powder (CL-P, Alpha Lipid Lifeline Colostrum, New Zealand) on growing performance, carcass weight and yield, organ weights, serum vitamins and malondialdehyde (MDA) levels in quails (Coturnix coturnix japonica). A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Colostrum feeding will provide enough IgG to the neonate goat kid until his immune system will be able to generate it by himself (Moretti et al 2013). Also, colostrum has been used as a supplement in other species (Akdemir et al 2018). An adequate colostrum feed is related with positive repercussions on growth, health and a reduction in mortality rate (Arguello et al 2004;Furman-Fratczak et al 2011;Nagyova et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Colostrum feeding will provide enough IgG to the neonate goat kid until his immune system will be able to generate it by himself (Moretti et al 2013). Also, colostrum has been used as a supplement in other species (Akdemir et al 2018). An adequate colostrum feed is related with positive repercussions on growth, health and a reduction in mortality rate (Arguello et al 2004;Furman-Fratczak et al 2011;Nagyova et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous research, we found that the addition of powdered colostrum increased final body weight, body weight gain, cumulative feed intake, cold carcass weight, cold carcass yield, and decreased feed efficiency in quails [19] . Similarly, in the present study we observed that LiqC supplementation increased body weight gain, and decreased feed efficiency in quails with increasing dietary LiqC supplementation for 42 days of the experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…Increased consumer demand for foods that promote nutrition and health encourages food manufacturers and researchers to innovate safe and cost-effective food that can provide multiple benefits in a single entity [ 69 ]. Consequently, bovine colostrum (BC) and its derivatives have attracted researchers to use their biologically active constituents to make functional food and feed supplements [ 28 ]. BC is widely used as a food and feed supplement, and it is regarded as safe from a toxicological point of view [ 70 ].…”
Section: Bovine Colostrum As Modern Deliverable Nutraceutical Formula...mentioning
confidence: 99%
“…Besides the aforementioned, researchers across the globe continuously focus on formulating feed with bioactive constituents for Aves. A recent study examining the supplementation effect of BC powder on the performance, serum lipid peroxidation level, and carcass yield in Japanese quail was conducted by Akdemir et al [ 28 ]. For the experiment, Japanese quail ( n = 90) were divided into three subgroups and supplemented with a basal diet, a basal diet with 2.5% BC powder, and a basal diet with 5% BC powder for 42 days.…”
Section: Bovine Colostrum As Modern Deliverable Nutraceutical Formula...mentioning
confidence: 99%
See 1 more Smart Citation